2023
DOI: 10.1371/journal.pdig.0000194
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of internet delivered cognitive behaviour therapy provided as routine care for people in the depressed phase of bipolar disorder treated with Lithium

Abstract: There is little research reporting the outcome of internet delivered cognitive behaviour therapy, (iCBT), which helps patients identify and modify unhelpful cognitions and behaviours, for the depressed phase of bipolar disorder as part of routine care. Demographic information, baseline scores and treatment outcomes were examined for patients of MindSpot Clinic, a national iCBT service who reported taking Lithium and their clinic records confirmed the diagnosis of bipolar disorder. Outcomes were completion rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…This treatment deals with the cognitive and behavioral patterns of BD [101]. In several randomized controlled trials (RCTs), CBT has been shown to decrease the severity of depression and improve some of the functions of BD [102], but CBT may be less effective with high severity of BD or those with multiple episodes. Some findings indicate that CBT is an effective treatment for depression episodes in BD, but its effectiveness for mania episodes is questionable [98].…”
Section: Cognitive Behavioral Therapymentioning
confidence: 99%
“…This treatment deals with the cognitive and behavioral patterns of BD [101]. In several randomized controlled trials (RCTs), CBT has been shown to decrease the severity of depression and improve some of the functions of BD [102], but CBT may be less effective with high severity of BD or those with multiple episodes. Some findings indicate that CBT is an effective treatment for depression episodes in BD, but its effectiveness for mania episodes is questionable [98].…”
Section: Cognitive Behavioral Therapymentioning
confidence: 99%